2021
DOI: 10.3390/nano11020498
|View full text |Cite
|
Sign up to set email alerts
|

Chemically-Gated and Sustained Molecular Transport through Nanoporous Gold Thin Films in Biofouling Conditions

Abstract: Sustained release and replenishment of the drug depot are essential for the long-term functionality of implantable drug-delivery devices. This study demonstrates the use nanoporous gold (np-Au) thin films for in-plane transport of fluorescein (a small-molecule drug surrogate) over large (mm-scale) distances from a distal reservoir to the site of delivery, thereby establishing a constant flux of molecular release. In the absence of halides, the fluorescein transport is negligible due to a strong non-specific in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 78 publications
(104 reference statements)
0
5
0
Order By: Relevance
“…20 The good electric conductivity, though often overshadowed by other outstanding properties, has been identified through careful impedance analyses as a crucial factor in the homogenization of the oxidation reaction of BNP Zn anodes 3,13 and the stabilization of BNP Ir during the electrocatalysis of oxygen evolution, 76 partly because in both cases the metals were partly converted to poorly conductive oxides. In the pores, conductivities or diffusivities of common electrolytes and molecules were determined to be generally around 30−50% of the bulk values for BNP Au samples (mostly of φ p ∼ 0.5), 22,60,77 although I cannot further narrow down the range given the differences in the diffusing molecules or ions, the structures, and the measurement methods. All these results support the high conductivities due to the bicontinuity but reveal no clear structural dependence as of yet.…”
Section: ■ the Bicontinuitymentioning
confidence: 95%
See 3 more Smart Citations
“…20 The good electric conductivity, though often overshadowed by other outstanding properties, has been identified through careful impedance analyses as a crucial factor in the homogenization of the oxidation reaction of BNP Zn anodes 3,13 and the stabilization of BNP Ir during the electrocatalysis of oxygen evolution, 76 partly because in both cases the metals were partly converted to poorly conductive oxides. In the pores, conductivities or diffusivities of common electrolytes and molecules were determined to be generally around 30−50% of the bulk values for BNP Au samples (mostly of φ p ∼ 0.5), 22,60,77 although I cannot further narrow down the range given the differences in the diffusing molecules or ions, the structures, and the measurement methods. All these results support the high conductivities due to the bicontinuity but reveal no clear structural dependence as of yet.…”
Section: ■ the Bicontinuitymentioning
confidence: 95%
“…89 The interface between a BNP metal and an electrolyte, controllable through the electrolyte composition and the applied potential, can thereby influence the transport of ions, 90 enabling selectivity for sensing and controlled molecule release for drug delivery. 22,27 The nanostructures are also versatile substrates for light−matter interactions at the surfaces for a broad range of sensing and photonic applications. 91 At the small length scale, bicontinuity is realized through extremely large negative and positive curvatures, which necessitate many surface defects.…”
Section: ■ the Bicontinuitymentioning
confidence: 99%
See 2 more Smart Citations
“…Actually, nanoporous gold (np-Au) electrodes exhibited the anti-biofouling effect for albumin [e.g., bovine serum albumin, 10% fetal bovine serum, and human serum albumin (HSA)] and human serum in electrochemical measurements. [21][22][23][24][25][26] This means that the electron transfer that small redox molecules cause at gold surfaces was hindered at planar (bare) gold electrodes but not at np-Au electrodes because more proteins nonspecifically covered the bare gold surface compared with the np-Au surface. It was also reported that the pore size of the np-Au electrode was comparable to that of BSA, showing the anti-biofouling effect.…”
mentioning
confidence: 99%